The principle of solidarity and its relevance for tissue research - Prainsack, Barbara (Henry Stewart Talks, 2015)
Challenges in tissue research: societal aspects, Consent and autonomy, The issue of tissue donation, Solidarity in the perspective of tissue donation and biochemical research, Recruitment of tissue donors, Data protection